Government Calling Revisited: A Survey-Experiment on the Moderating Role of Public Service Motivation in Assessing Employer Attractiveness - Vandenabeele, Wouter; Jager, Stefanie (Frontiers in Psychology, 2020)
Employer attractiveness is an important variable for any organization. It is therefore not surprising that organizations try to control this facet when communicating recruitment messages for positions to be filled. This study aims to capture this process for public sector organizations, while looking at the role that a particular type of prosocial motivation – public service motivation: the motivation people have to contribute to society – plays in this process. To this end, a survey-experiment (N = 192) with prospective employees is carried out in which recruitment messages with three different value statements (public, private, neutral) are presented to the respondents. The effect of these message on both attractiveness and person–organization fit, as moderated by public service motivation, is tested. The results indicate that public service motivation indeed moderates the effect of these messages. However, the results do not fully corroborate the theoretical expectations. Therefore, additional exploratory analyses are performed in order to better understand the variables included in this process. This provides a direction for further research. Theoretical and practical implications are discussed.